2018
DOI: 10.3390/ijms19092769
|View full text |Cite
|
Sign up to set email alerts
|

Telocinobufagin and Marinobufagin Produce Different Effects in LLC-PK1 Cells: A Case of Functional Selectivity of Bufadienolides

Abstract: Bufadienolides are cardiotonic steroids (CTS) identified in mammals. Besides Na+/K+-ATPase inhibition, they activate signal transduction via protein–protein interactions. Diversity of endogenous bufadienolides and mechanisms of action may indicate the presence of functional selectivity and unique cellular outcomes. We evaluated whether the bufadienolides telocinobufagin and marinobufagin induce changes in proliferation or viability of pig kidney (LLC-PK1) cells and the mechanisms involved in these changes. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 99 publications
2
15
0
Order By: Relevance
“…This isoform is possibly the only one expressed in peritoneal macrophages [39]. Additionally, we have shown here and elsewhere [25, 40] that marinobufagenin is 20-80 times less potent than ouabain. Indeed, 1 mM marinobufagenin did not inhibit the murine Na + /K + -ATPase α 1 isoform, and the inhibition of the other isoforms, α 2 and α 3, only begins at around 1 μ M (IC 50 = 3.8 μ M).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…This isoform is possibly the only one expressed in peritoneal macrophages [39]. Additionally, we have shown here and elsewhere [25, 40] that marinobufagenin is 20-80 times less potent than ouabain. Indeed, 1 mM marinobufagenin did not inhibit the murine Na + /K + -ATPase α 1 isoform, and the inhibition of the other isoforms, α 2 and α 3, only begins at around 1 μ M (IC 50 = 3.8 μ M).…”
Section: Discussionsupporting
confidence: 60%
“…Differences of the affected cytokines may be associated with the pharmacological profile of these steroids. We have recently shown that structurally related bufadienolides generate distinct cellular effects probably by a particular selection of intracellular signaling pathways, which is called functional selectivity [25]. At last, the reduction in cytokine levels and polymorphonuclear migration caused by marinobufagenin suggests an anti-inflammatory role in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hepatoma, gallbladder carcinoma and lung cancer (16). in previously published studies, bufadienolide compounds have been demonstrated to induce arrest of the tumor cell cycle and apoptosis (17,18). in addition, bufadienolides were revealed to markedly inhibit proliferation and induce autophagy in liver cancer cells (19), and alterations in the expression levels of microtubule-associated proteins 1a/1B light chain 3-ii (lc3-ii), p62, Bax, Bcl-2, cyclin d1 and caspase-3 are involved in the underlying mechanism (20).…”
Section: Bufadienolides Induce Apoptosis and Autophagy By Inhibiting mentioning
confidence: 98%